(untitled) (Bangladesh Journal of Medical Science, 2012)
Multiple idiopathic cervical resorption (MICR) is a disease of the tooth in which there is progressive cervical resorption of multiple teeth leading to exfoliation of crown. The etiological factors for such a resorption are various but the lack of definitive single etiological factor/disease process makes management of such processes extremely difficult. A flap surgery followed by restoration with glass ionomer cement was carried out for the cessation of resorption process, finally a cast partial denture was delivered for prosthetic rehabilitation. DOI: http://dx.doi.org/10.3329/bjms.v11i2.8680 Bangladesh Journal of Medical Science Vol. 11 No. 02 April 2012: 151-153